Biometric Recognition 10th Chinese Conference, CCBR 2015, Tianjin, China, November 13-15, 2015, Proceedings - Yang, Jinfeng; Yang, Jucheng; Sun, Zhenan; Shan, Shiguang; Zheng, Weishi; Feng, Jianjiang (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2015)
This book constitutes the refereed proceedings of the 10th Chinese Conference on Biometric Recognition, CCBR 2015, held in Tianjin, China, in November 2015. The 85 revised full papers presented were carefully reviewed and selected from among 120 submissions. The papers focus on face, fingerprint and palmprint, vein biometrics, iris and ocular biometrics, behavioral biometrics, application and system of biometrics, multi-biometrics and information fusion, other biometric recognition and processing.  .